Evaluation of gamma irradiation on the microbiological, phytochemicals, and aromatic profiles of sun-bleached preserved pepper (Capsicum annuum L.) - Mengyun Ouyang; Sheng Cao; Yiji Zhou; Mo Mo; Yuanfang Xu; Qiling Zhang; Yong Zhang; Chao Deng; Feng Guo; Hui Song; Yan Wang; Yiqun Huang; et al. (Food Chemistry, 2026)

Genome-wide identification of the cation proton antiporter (CPA) gene family in Setaria italica and potential function analysis of SiNHX3 gene - Sheng Zheng; Haiyan Tie; Qiling Wang; Shangli Chai; Mingxiao Wang; Sirui Wang; Teng-Guo Zhang; Guofan Wu (Journal of Plant Physiology, 2026)

Bisphenol A disrupts the neuronal F-actin cytoskeleton by activating the RhoA/ROCK/LIMK pathway in Neuro-2a cells - Yi Guo; Yuxin Wang; Qian Li; Qiling Liu; Xuyuan Zhang; Jiajia Ren; Chong Wang (Toxicology, 2024)

Critical windows for exposure to chemical composition of ambient particulate matter and human semen quality decline - Lingxi Wang; Qiling Wang; Yunchong Yao; Jiayi Zhou; Xiaoyan Cai; Tingting Dai; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Pi Guo; et al. (Science of The Total Environment, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

The role of phosphorus speciation of biochar in reducing available Cd and phytoavailability in mining area soil: Effect and mechanism - Kan Huang; Xuecheng Sun; Jingguo Sun; Yali Guo; Xiaoming Hu; Chengxiao Hu; Qiling Tan (Science of The Total Environment, 2023)

Sperm quality decline associated with gaseous pollutant exposure: Evidence from a large cohort multicenter study - Xiaoyan Cai; Haobo Ni; Qiling Wang; Tingting Dai; Lingxi Wang; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Lina Xiao; Ting Xu; et al. (Journal of Hazardous Materials, 2023)

Singlet oxygen triggered by carbon doped boron nitride nanosheets for enhanced removal of tetracycline by peroxymonosulfate activation - Qiling Zheng; Jinghua Guo; Xiaohua Ren; Weijie Zhang; Hongjie Qin; Penghui Zhang; Shouwei Zhang; Xijin Xu (Journal of Environmental Chemical Engineering, 2023)

Contribution of tree species to the co-occurrence network of the leaf phyllosphere and soil bacterial community in the subtropical forests - Jianqing Wang; Xiuzhen Shi; Manuel Esteban Lucas-Borja; Qiling Guo; Liyan Wang; Zhiqun Huang (Journal of Environmental Management, 2023)

Exosomes Derived from Human Amniotic Mesenchymal Stem Cells Facilitate Diabetic Wound Healing by Angiogenesis and Enrich Multiple lncRNAs - Shangfeng Fu; Hongyan Zhang; Xiancai Li; Qiling Zhang; Chunyan Guo; Keqing Qiu; Junyun Feng; Xiaoxiao Liu; Dewu Liu (Tissue Engineering and Regenerative Medicine, 2023)

Soil nematode abundances drive agroecosystem multifunctionality under short‐term elevated CO 2 and O 3 - Jianqing Wang; Xiuzhen Shi; Manuel Esteban Lucas‐Borja; Qiling Guo; Jiaoyan Mao; Yunyan Tan; Guoyou Zhang (Global Change Biology, 2023)
The response of soil biotas to climate change has the potential to regulate multiple ecosystem functions. However, it is still challenging to accurately predict how multiple climate change factors will affect multiple ecosystem functions. Here, we assessed the short‐term responses of agroecosystem multifunctionality to a factorial combination of elevated CO 2 (+200 ppm) and O 3 (+40 ppb) and identified the key soil biotas (i.e., bacteria, fungi, protists, and nematodes) concerning the changes in the multiple ecosystem functions for two rice varieties (Japonica, Nanjing 5055 vs. Wuyujing 3). We provided strong evidence that combined treatment rather than individual treatments of short‐term elevated CO 2 and O 3 significantly increased the agroecosystem multifunctionality index by 32.3% in the Wuyujing 3 variety, but not in the Nanjing 5055 variety. Soil biotas exhibited an important role in regulating multifunctionality under short‐term elevated CO 2 and O 3 , with soil nematode abundances better explaining the changes in ecosystem multifunctionality than soil biota diversity. Furthermore, the higher trophic groups of nematodes, omnivores‐predators served as the principal predictor of agroecosystem multifunctionality. These results provide unprecedented new evidence that short‐term elevated CO 2 and O 3 can potentially affect agroecosystem multifunctionality through soil nematode abundances, especially omnivores‐predators. Our study demonstrates that high trophic groups were specifically beneficial for regulating multiple ecosystem functions and highlights the importance of soil nematode communities for the maintenance of agroecosystem functions and health under climate change in the future.

Down-regulation of SETD6 protects podocyte against high glucose and palmitic acid-induced apoptosis, and mitochondrial dysfunction via activating Nrf2-Keap1 signaling pathway in diabetic nephropathy - Xiang Wang; Qiling Liu; Deqin Kong; Zi Long; YuFang Guo; Shuang Wang; Rui Liu; Chunxu Hai (Journal of Molecular Histology, 2020)

Modeling fertilization impacts on nitrate leaching and groundwater contamination with HYDRUS-1D and MT3DMS - Han Zhang; Ruxing Yang; Shanshan Guo; Qiling Li (Paddy and Water Environment, 2020)

Groundwater pollution source apportionment using principal component analysis in a multiple land-use area in southwestern China - Qiling Li; Han Zhang; Shanshan Guo; Kang Fu; Lei Liao; Yi Xu; Siqian Cheng (Environmental Science and Pollution Research, 2020)